2000
DOI: 10.1159/000016597
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Reduction of Enamel Demineralization by Calcium and Phosphate in vitro

Abstract: In theory, calcium and phosphate in the plaque fluid exert a large influence on the demineralization of enamel surface. In order to know the effect of increasing the concentration of either of these factors, the following in vitro experiment was conducted. Three thin sections, about 150 Ìm thick, were cut out from each of 13 human premolars. All surfaces of the sections, except for the original enamel surface, were coated with nail varnish. These sections were immersed into one of two sets of demineralizing so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
1
18
0
3
Order By: Relevance
“…an equivalent effect [Tanaka and Kadoma, 2000]. Our fi ndings indicate that the acid-gel systems are similar to plaque in that calcium activity was a relatively small fraction of total calcium concentration.…”
Section: Discussionmentioning
confidence: 49%
“…an equivalent effect [Tanaka and Kadoma, 2000]. Our fi ndings indicate that the acid-gel systems are similar to plaque in that calcium activity was a relatively small fraction of total calcium concentration.…”
Section: Discussionmentioning
confidence: 49%
“…Some authors have observed that a small change in the degree of saturation resulted in a difference in the dissolution of enamel and that it is an important parameter that defines the ability of a solution to demineralize enamel [Barbour et al, 2003;Finke et al, 2000;Margolis et al, 1999;Tanaka and Kadoma, 2000]. Only in a small volume of the beverages would a significant rise in saturation be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Although Robinson's and Ribena ToothKind have comparable phosphate concentrations, phosphate has been shown to be less effective at reducing enamel erosion than calcium. 15,18 .…”
Section: Discussionmentioning
confidence: 99%